2013
DOI: 10.1159/000351685
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Neck and Jaw Muscle Modulation of Tinnitus

Abstract: Forceful contractions of neck and jaw muscles have consistently been shown to modulate tinnitus and can be used to screen patients who are responsive to somatic stimulation and, therefore, optimal candidates for somatosensory-based treatment. To identify the factors associated with somatic modulation of tinnitus, 163 patients underwent 19 neck and jaw maneuvers after an extensive physiological and audiological profile was compiled. Overall, tinnitus was modulated in 57.1% of ears tested. Unilateral tinnitus sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 35 publications
8
40
3
4
Order By: Relevance
“…This case demonstrates that tinnitus modulation can be found even when no somatic disorder is present; in fact, somatic modulation of tinnitus is a widespread condition that can be present with or without underlying somatic disorders 31,40 . Furthermore, as previously discussed, several authors reported a large capability of somatic tinnitus modulation in multiple patient series ranging between 65.3% and 83.3% 32,35,[41][42][43]45,47,61,65 . In this patient, the negative history for self-reported somatic disorder suggests caution while taking into account a somatic origin for his tinnitus.…”
Section: Comments On This Casesupporting
confidence: 53%
See 2 more Smart Citations
“…This case demonstrates that tinnitus modulation can be found even when no somatic disorder is present; in fact, somatic modulation of tinnitus is a widespread condition that can be present with or without underlying somatic disorders 31,40 . Furthermore, as previously discussed, several authors reported a large capability of somatic tinnitus modulation in multiple patient series ranging between 65.3% and 83.3% 32,35,[41][42][43]45,47,61,65 . In this patient, the negative history for self-reported somatic disorder suggests caution while taking into account a somatic origin for his tinnitus.…”
Section: Comments On This Casesupporting
confidence: 53%
“…Patients with somatic tinnitus have shown different characteristics, being younger, with higher prevalence of female gender and unrelated to hearing loss (somatic tinnitus patients often have normal hearing) or tinnitus severity [58][59][60][61][62] . The most common musculoskeletal conditions that underlie somatic tinnitus are temporomandibular joint (TMJ) and cervical spine (NECK) disorders 43,44,52 .…”
Section: Considerations On Somatic Modulation Of Tinnitusmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 This can be used to identify a subgroup of patients with tinnitus who are responsive to somatic stimulation and, therefore, are optimal candidates for somatosensorybased treatment. 7 Interestingly, osteopathic physicians have studied this connection and have used manual manipulative medicine to help patients with somatic tinnitus. 8 Acupuncture is a modality of somatosensory-based treatment, and Levine et al 9 opined that many of the patients with tinnitus who are responders to acupuncture are, in fact, people with somatically induced tinnitus.…”
Section: Introduction Wmentioning
confidence: 99%
“…16,17 The modulation of tinnitus by somatic movements is widely diffused among acute and chronic tinnitus sufferers and has been reported to involve one to two-thirds of them with different patient series ranging between 65% and 83%. [18][19][20][21][22] Several authors have developed sets of maneuvers to modulate tinnitus; a detailed description of these maneuvers has been published by Won in 2013 comparing the prevalence and characteristics of somatic modulation found in six previous studies.…”
Section: Introductionmentioning
confidence: 99%